Effects of Active Sitting Chairs on Short-Duration Computer Task Performance, Postural Risks, Perceived Pain, Comfort and Fatigue. (September 2017) - Kar, Gourab; Peditto, Kathryn S.; Guria, Sanjay; Callan, Jacqueline R.; Fronsman, Andrea E.; Lee, Serena Seo Hyon; Stohler, Justine; Moon, Dan; Li, Manwen; Cackett, Megan A.; Hedge, Alan
This study evaluated the effects of active and static sitting chairs on short-duration computer task performance, postural risks and perceived pain, comfort and fatigue. A repeated-measures, within-subjects study was conducted, in which 16 participants performed 40 trials of a computer-based homing task in four seating conditions. Computer task performance was operationalized using mousing and typing speed as the measures, postural risk was evaluated using the Rapid Upper Limb Assessment (RULA). Perceived scores for pain, comfort and fatigue were reported through a survey administered at baseline and after each seated task condition. Results suggest that for short-duration computer tasks, active seating does not reduce mousing and typing speed; postural risks for musculoskeletal disorders do not significantly differ in comparison to static seating. Additionally, while there is reduction in perceived levels of comfort for active seating, the perception of pain and fatigue do not change significantly.